The question as a tool for “appreciation”, the basis of academic culture - Jirón Beirute, Nicole (2020)
In this article, “the question” is problematized as a didactic resource for the motivation of dialogic experiences of education-transformation in the Escuela de Estudios Generales of University of Costa Rica. From the use of the question it is possible to become an active participant in the student body of the learning process, which it breaks with the hierarchy of power of the teacher-student response vector; it provokes a context of curiosity, respect and modesty to approach new fields of knowledge; it stimulates the appreciation for "otherness" which is nothing other than the humanization of human difference; it motivates hope as long as it provokes a creative act with “others” that it respects; it visualize students as political subjects of their time. This article shows the generation of appreciation for “otherness” stands out, which is considered the basis of the development of academic culture with a humanistic perspective; fundamental piece of the political educational project of the University of Costa Rica.